Literature Review: Neuromuscular Taping and Exercise for Diabetes Mellitus - Zulikha, Nora Eny; Rahayu, Umi Budi; Haqi, Nadyastama Faisal (FISIO MU: Physiotherapy Evidences, 2026)
Introduction: This literature review study was motivated by global health challenges such as diabetes mellitus (DM), which has become a significant global health issue, particularly in Indonesia, which ranks seventh in the world. Complications from DM, such as diabetic neuropathy, drastically affect patients' quality of life. Non-pharmacological approaches, such as neuromuscular taping therapy (NMT) and physical exercise, can reduce the risk of complications and thus be an effective additional solution in DM management. Methods: The literature review method was applied to five articles obtained from several databases, namely ResearchGate and Google Scholar. The search keywords for articles included NMT, Exercise, and Diabetes Mellitus. The researchers used "AND" as the Boolean Operator. Results: The findings of the literature review indicate that the application of NMT significantly improves microcirculation, balance, and proprioception, as well as reducing neuropathic pain in patients. In addition, the combination of NMT with non-pharmacological interventions such as Progressive Muscle Relaxation (PMR) and foot exercises can also reduce swelling and diabetic neuropathic pain. NMT with exercise shows greater improvement in Ankle Brachial Index (ABI) values and patient quality of life. Conclusion: NMT combined with exercise has been proven effective. NMT provides an effective and safe alternative for improving the quality of life of diabetic patients.